(untitled) (Asian Journal of Medical and Biological Research, 2020)
A survey was conducted in the three district of south western region of Bangladesh like Khulna, Satkhira and Bagerhat, to observe the socioeconomic condition and problems facing by the chicken farmers under the existing management practices. Five hundred commercial chicken farms were considered in the present study. Data were collected using a pretested questionnaire by interview of the farmers. To observe the socioeconomic conditions, the age of selected farmers, their gender, occupation, education level, land size, annual income from chicken farms, experience, training exposure and bio-security score were considered. There are two problems are categorized like diseases outbreaks and socioeconomic problems. Among the respondents, maximum percentage of farmers were male groups within 31 to 40 years age had conjugated with the occupation of poultry and agriculture and belonged to HSC level of education. Highest percentage of medium land size farmer earned 01-03 lac BDT per year only from the chicken farms. Newcastle or Ranikhet disease was highly severed followed by Fowl cholera, Gumboro and Coccidiosis. Irregular fluctuation of market price was the major problem facing by the chicken farmer in the study area. Bio-security practice and proper marketing system should enhance the profitability of the chicken farms. Asian J. Med. Biol. Res. September 2020, 6(3): 507-513